2012
DOI: 10.1308/003588412x13171221592410
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery programmes in hepatobiliary and pancreatic surgery: a systematic review

Abstract: INTRODUCTIONThe terms ‘enhanced recovery after surgery’, ‘enhanced recovery programme’ (ERP) and ‘fast track surgery’ refer to multimodal strategies aiming to streamline peri-operative care pathways, to maximise effectiveness and minimise costs. While the results of ERP in colorectal surgery are well reported, there have been no reviews examining if these concepts could be applied safely to hepatopancreatobiliary (HPB) surgery. The aim of this systematic review was to appraise the current evidence for ERP in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 37 publications
4
57
0
Order By: Relevance
“…Four previous systematic reviews [42][43][44][45] have explored this theme by now; however, these previous reviews included no RCTs (Coolsen et al 45 included two RCTs that did not purely compared FT programs with CS programs-both control and experimental groups in these two RCTs were all treated with FT programs) and analyzed some case-control studies or retrospective case series studies that solely discussed the effects of FTS programs without setting a control group, this may reduce the potency of systematic review. A recent systematic review 46 contained two RCTs and published in 2014, also investigated this topic and showed more cogency than previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Four previous systematic reviews [42][43][44][45] have explored this theme by now; however, these previous reviews included no RCTs (Coolsen et al 45 included two RCTs that did not purely compared FT programs with CS programs-both control and experimental groups in these two RCTs were all treated with FT programs) and analyzed some case-control studies or retrospective case series studies that solely discussed the effects of FTS programs without setting a control group, this may reduce the potency of systematic review. A recent systematic review 46 contained two RCTs and published in 2014, also investigated this topic and showed more cogency than previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…These programs use a multimodal approach to maximize effectiveness and minimize cost, thus optimizing perioperative care pathways [6]. ERAS programs have been associated with reduced complication rates, hospital stays, and hospital costs [1].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, ERAS protocols were subsequently extended to other types of surgery, including gastric 6 , pancreatic 7 and liver 8 surgery. The use of ERAS protocols in liver surgery appeared to be safe and feasible [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%